Drop jumps or hurdle jumping for volleyball training? - Viitasalo, J.; Hamalainen, K. (1992)
Drop jumps and hurdle jumping are drills widely used in volleyball training. Selection of dropping height or hurdle jumping technique has often been based on traditions rather than detailed biomechanical analysis. This study was designed to compare volleyball spiking and blocking with the jumping drills mentioned above in relation to variouskinematic and kinetic parameters and myoelectrical activity (EMG).